Letter From the Editor - Regina Hoffman (Patient Safety, 2021)
The world as we knew it is only a distant memory. It has been a year since everything changed. Kids came home from school—some are still home. Meetings moved from downtown conference rooms to overcrowded dining rooms. Toilet paper almost became a black-market commodity. Our healthcare workers and healthcare systems were pushed beyond their limits. A half million people died in the United States alone and millions more recovered. Some initiatives were put on hold and others fast-tracked through what in “normal” times would take years. One thing is for certain, none of us are the same. And although we are not the same, there are passions that we continue to share.